EFFECT OF GAMMA IRRADIATION ON CHROMOSOMAL ABERRATIONS RATS ON THE BACKGROUND OF PYRIDOXINE - Костюк, С.С. (World of Medicine and Biology, 2014)
In this paper we studied chromosomal aberrations (chromosome and hromatydni) rats under the influence of gamma irradiation on the background of pyridoxine. Methods. The study was conducted on 10 white male rats Wistar, weighing 150-200 g animals were divided into two groups. The first group, the control, the second pilot, who the week before and one day after irradiation was administered intramuscular Pyridoxin monochloride at a dose of 600 mg kh.masy body. Chromosomal aberrations investigated by methods provided in the guidance for laboratory work on special course "cytogenetics" [4]. In studies using klohitsyn. In rats, washed red bone marrow, stained and examined chromosome. Results. Installed significant chromosomal aberrations under the influence of gamma-irradiation. The use of pyridoxine as radioprotector significantly reduces both chromosomal and hromatydni aberrations in rats, confirming the radioprotective property of vitamin B6.